Coping together with hearing loss: a qualitative meta-synthesis of the psychosocial experiences of people with hearing loss and their communication partner - Barker, Alex; Leighton, Paul; Ferguson, Melanie A. (Taylor & Francis, 2017)
Objective – To examine the psychosocial experiences of hearing loss from the perspectives of both the person with hearing loss and their communication partner. Design - A meta-synthesis of the qualitative literature. Study Sample – From 880 records, twelve qualitative papers met the inclusion criteria, (i) adults with hearing loss, communication partners, or both, and (ii) explored psychosocial issues. Results - Four themes related to the psychosocial experience of hearing loss were found, (i) the effect of the hearing loss, (ii) the response to hearing aids, (iii) stigma and identity, and (iv) coping strategies. Hearing loss affected both people with hearing loss and communication partners. Hearing aids resulted in positive effects, however, these were often outnumbered by negative effects. Non-use of hearing aids was often influenced by stigma. Coping strategies used were related to how the person with hearing loss perceived their self and how the communication partner perceived the relationship. Aligned coping strategies appeared to have a positive effects.